PERSENTASE POST LARVA UDANG GALAH SEBAGAI PEMBENTUK POPULASI SINTETIS G1 DARI SUMBER GENETIK SUNGAI PAGATAN, KINTAP DAN BARITO - Anny Rimalia; Mukhlisah Mukhlisah; Yulius Kisworo (EnviroScienteae, 2016)
This study aims to determine the percentage of post-larva Giant Freshwater Prawn (Macrobrachium Rosenberg de Man) from genetic resources of  Kintap River, Pagatan River and Barito River. This study uses a completely randomized design with three treatments and three replications. The treatments were tested A: Genetic Resources Pagatan (Pg), B: Genetic Resources Kintap (Kt) and C: Genetic Resources Barito (Br). The results showed the genetic resources percentage  post larvae Pagatan provide the highest 76,67%, followed Barito and Last  Genetic Resources of Kintap 66,00%.  ANOVA results showed different genetic sources of influence on percentage post-larva. The results LSD test indicate  percentage Post Larvae was produced from  genetic source Pagatan different from the genetic resources Kintap, then genetic resources Pagatan not different from genetic resources Kintap, and so  percentage Post Larvae of genetic resources Barito not  different from the genetic source Kintap.